Pengaruh Minat Belajar dan Efikasi Diri Terhadap Hasil Belajar Matematicka Peserta Didik Kelas V Sekolah Dasar - Jody Setya Hermawan; Maman Surahman; Riswanti Rini; Fitriyah Amaliyah; Marti Fitria Rohmah (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2023)
The problem in this study is that most students in Grade V of SD Negeri Gugus Mawar Kecamatan Natar, did not achieve the KKM in the Odd Semester Final Assessment T.A 2022/2023 in Mathematics. This study aims to analyse and describe the effect of interest in learning and self-efficacy on mathematics learning outcomes. This research is an ex post facto correlational research using a quantitative approach. This research was conducted in state elementary schools in Mawar sub-district, Natar district in the even semester of T.A. 2022/2023. The population in this study were all fifth grade students of SD Negeri Gugus Mawar Kecamatan Natar with a total of 134 students. The sample used was 95 students consisting of 51 male students and 44 female students. The data collection instrument used was a questionnaire with a Likert scale, which was then analysed using the regression formula. The results showed a positive and significant influence between learning interest and self-efficacy simultaneously on the mathematics learning outcomes of fifth grade students of state elementary schools, with an influence of 57.6%. The results of this study indicate that learning interest and self-efficacy have a positive influence on mathematics learning outcomes, so efforts should be made to increase students' learning interest and self-efficacy in order to achieve more optimal learning outcomes.